Improve Energy Efficiency In Cooperative Medium Access Control Protocol For Wireless Networks - Oluwole, Akande Damilare (2019)
Cooperative communication has drawn a substantial attention in recent years due to the efficient and optimal utilization of constraint resources in dynamic wireless networks at a reduced infrastructural deployment and cost. In the medium access control (MAC) layer perspective, two major problems are associated with cooperative networks. The ability of cooperative MAC (CMAC) protocols to achieve multi-objective target orientation limit their adaptation to the future generation of wireless networks, since most of the existing protocols focus only on a single target objective. Besides, the sustainability of energy-constrained wireless networks due to limited energy supply capacity hinders their performance to ensure stable and reliable communication. These aforementioned problems limit the adaptation of the existing protocols to fit into the future generation of wireless networks. To adequately address these problems, two distinct CMAC protocols are proposed in this thesis to cater for the unpredictable and dynamic nature of the wireless network. Firstly, a new network lifetime-aware CMAC protocol named LEA-CMAC is proposed for energy-constrained wireless ad-hoc networks. An optimization problem is formulated with an objective of extending the lifetime of the network. The solution to this non-linear problem is provided in terms of optimal transmit power at the source and relay terminals in symmetric and asymmetric transmit power policies. The solution provided by this protocol is limited in terms of energy efficiency and network lifetime since the network totally rely on the helper nodes limited-powered batteries for their transmissions. Secondly, a novel CMAC protocol with radio frequency (RF) energy harvesting (EH) capability named EH-CMAC is proposed in a reactive relaying energy-constrained wireless ad-hoc networks to address the limitation in the earlier proposed LEA-CMAC protocol. The protocol possesses the ability to ensure a sustainable and reliable wireless connectivity in a dynamic wireless environment through the selection of an appropriate transmission mode that best suits the instantaneous network requirement. The protocol comprises of two distinct energy-efficient techniques namely, the outage probability quality-of-service (QoS) requirement and the transmit power optimization techniques which are applied in both traditional and EH relaying schemes. These techniques are selected and adapted based on the instantaneous network information and target objectives. In addition, a distributed and adaptive relay selection backoff process is proposed in each case to satisfy the available network information and achieve a multi-objective target oriented protocol. Through extensive simulation and comparison with existing CMAC protocols, the results show that LEA-CMAC extend the network lifetime by 85.67% over an existing CMAC protocol, while EH-CMAC extends the network lifetime by 90.99% over a traditional CMAC protocol. Thus, both protocols achieve a multi-objective target orientation under general circumstances.